Online Measuring Of Grain Flowrates and Its Measurement Sensitivities with Pitch and Roll Angles - Reni Eka Putri; Azmi Yahya; Nor Maria Adam; Samsuzana Abd Aziz (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2021)
A complete calibration test stand was constructed and instrumented to examine the effect of varying pitch and roll positions on the measurement errors of a microwave solid type flow sensor. Results indicated that measurement errors ranging from 2.50% to 6.82% and 1.80% to 8.86% were obtained by the changing of chute pitch (descending and ascending) and roll angle positions from 1.5° to 4.5°, respectively. Greater measurement errors were found at the low screw auger conveyor speed range. However, the magnitude of errors is within the acceptable margin for any typical wet paddy land topography.